Current Topics on Military Medicine - Gorbunov, Nikolai V. (IntechOpen, 2021)
This book examines recent progress in understanding the epidemiology and pathophysiology of combat-related disorders with an emphasis on the development of advanced diagnostics and medical treatments. The chapters encompass personal experience and visions of the contributing authors. This book is for a broad audience of readers including students and military healthcare professionals.